2022
DOI: 10.1038/s41564-022-01184-y
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance genes in the gut microbiota of mothers and linked neonates with or without sepsis from low- and middle-income countries

Abstract: Early development of the microbiome has been shown to affect general health and physical development of the infant and, although some studies have been undertaken in high-income countries, there are few studies from low- and middle-income countries. As part of the BARNARDS study, we examined the rectal microbiota of 2,931 neonates (term used up to 60 d) with clinical signs of sepsis and of 15,217 mothers screening for blaCTX-M-15, blaNDM, blaKPC and blaOXA-48-like genes, which were detected in 56.1%, 18.5%, 0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 64 publications
2
32
0
Order By: Relevance
“…Maternal transmission has been implicated in ESBL-E acquisition by neonates by looking at prevalence [10], or by using matched antimicrobial resistance phenotypes [11], pulsed-field gel electrophoresis [12], repetitive element PCR typing [13] to compare strains between mother and infant. Most recently, the BARNARDS study identified identical isolates between mother and infant in E. coli using whole-genome sequencing, suggesting mother-to-child transmission in a large south Asian and African dataset [14].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal transmission has been implicated in ESBL-E acquisition by neonates by looking at prevalence [10], or by using matched antimicrobial resistance phenotypes [11], pulsed-field gel electrophoresis [12], repetitive element PCR typing [13] to compare strains between mother and infant. Most recently, the BARNARDS study identified identical isolates between mother and infant in E. coli using whole-genome sequencing, suggesting mother-to-child transmission in a large south Asian and African dataset [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria, Pakistan, Ethiopia, and the Democratic Republic of Congo collectively account for almost 50% of neonatal deaths worldwide (WHO, 2022). There is concern that this will increase to 20 million deaths yearly by 2050 (Carvalho et al, 2022).…”
mentioning
confidence: 99%
“…Some experts are worried there is a relationship between these infections and overuse of antibiotics around the world. Antibiotic resistance has been identified in mothers and neonates within hours of birth (Carvalho et al, 2022). Is sepsis related to scarce resources in low- and medium-income countries that can be used to adequately diagnose and treat newborn sepsis?…”
mentioning
confidence: 99%
See 2 more Smart Citations